Information-analytical aspects of the reception organisation of powder microcomposites on an iron basis - A.V. LYULKO; V.V. GRITSENKO; B.B. JMAILOV; V.G. LYULKO (Advanced Engineering Research, 2008)
The basic stages of a complex development direction of a science and practice of powder metallurgy as method of information-analytical representation of its basic aspects are presented. The basic algorithm of carrying out of operations and the scheme of the decision of tasks in view on object with some number of unknown factors is given. Ways of the further perfection of the presented technology of powder metallurgy and nanocomposite materials are planned.